DEVELOPMENT OF IMPROVED ROBOTICS EXTRUDER LOADING SYSTEM - KOVALYOV, Yuri; PLESHKO, Sergey; SUVOROV, Ivan (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The relevance of the study is due to the fact that the loading of granulated polymer material into the working hopper of extruders is mainly carried out manually from bags by production operators. The capacity of working hoppers of extruders is limited due to the fact that with a significant height of the bulk material, an increase in static pressure occurs in the lower layers, which leads to the formation of vaults, uneven supply of polymer into the material cylinder and deterioration of the quality of products. Since the work process of extrusion is continuous and lasts an entire work shift, there is a need to constantly control the filling level of the work hoppers of the extruders. The paper proposes a robotic extruder loading system for the processing of thermoplastic polymer materials into long products (pipes, profiles, films, etc.). The paper proposes a system for loading one or more extruders, which contains a large hopper loaded with raw materials for an entire work shift. From this hopper, the working hopper of the extruder is automatically filled with the help of a screw feeder. Automatic monitoring of the filling status of the hoppers is carried out by a microcontroller with the help of raw material level sensors. The object of research is the process of automatic control of periodic loading of loose materials into technological machines. The subject of the research is a robotic system for loading granulated polymers into the working hoppers of extruders. The purpose of the research is to develop a control system for devices for periodic dosing of granular polymer materials and loading them into working hoppers of limited capacity, which can be used in extruders. The task of the work is an analytical study of the effectiveness of the application of extruder loading systems based on a screw feeder and the development of its design and automatic control scheme. The methodological and theoretical basis of the research are the basic provisions of the theory of automatic control of technological processes, the design of transport equipment for loose media, and the basis of the calculation of machine parts. A scientific novelty is that the work proposed for the first time a device for automatic control of the extruder loading system based on a microcontroller with the possibility of programming the work algorithm. The results of the work can be used to create new systems for controlling the operation of equipment for processing polymer materials and creating new designs. The methodological and theoretical basis of the research are the basic provisions of the theory of automatic control of technological processes, the design of transport equipment for loose media, and the basis of the calculation of machine parts. A scientific novelty is that the work proposed for the first time a device for automatic control of the extruder loading system based on a microcontroller with the possibility of programming the work algorithm. The results of the work can be used to create new systems for controlling the operation of equipment for processing polymer materials and creating new designs.